UNA's 50th Anniversary: An International View - Morales-Camacho, María Fernanda (2023)
The Universidad Nacional is an institution characterized by humanism and inclusion as core principles that are explicit in the interest of supporting the most vulnerable sectors in society. This interest in the person and inclusion is not just the result of the national context but the legacy of previous institutions and the complex international background when the institution was founded. Thus, this Editorial aims to contextualize the history of Universidad Nacional by using some international issues considered as relevant due to its scope.